The interplay of stratal and vertical migration pathways in shallow hydrocarbon plumbing systems. (11th March 2021) - Sun, Qiliang; Cartwright, Joe; Foschi, Martino; Lu, Xiangyang; Xie, Xinong
Abstract: Hydrocarbon plumbing systems have been extensively documented in the past two decades using high‐resolution 3D seismic data, exploiting the ability of seismic imaging techniques to reveal the subsurface geometry of gas charged sediments. In this paper, we present a detailed study of a hydrocarbon plumbing system from the South China Sea, that involves both vertical and lateral (stratal) hydrocarbon migration in Miocene to Recent clastic sediments that comprise multilayer stacking of thinly layered clays, silts and sands. We show that a transtensive fault system that provides lateral seal for fault‐dip traps of deep Miocene reservoirs, and offers a vertical pathway for migration to shallower silty units. These silty units in turn form a 'spillway' in a regional, northward migration path. This path involves filling each shallow fault‐dip trap to spill point towards the fault tips, with stratal migration forced around the outer flanks of the fault‐related folds. Successive fill‐to‐spill leads to a continuous trail of amplitude anomalies that merge into a continuous, larger, gas‐charged anomaly pattern. The migrating gas finally accumulates within a zone bounded by a large boundary fault with full juxtaposition seal. The pattern of anomaly distribution suggests that the hydrocarbon migration has been active in the Late Pleistocene and is probably continuing at the present day. Hence this plumbing system may be one of very few examples described to date in which dynamic hydrocarbon migration pathways have been directly imaged by seismic data. Abstract : Successive fill‐to‐spill of hydrocarbon migration leads to a continuous trail of amplitude anomalies that merge into a continuous, larger, gas‐charged anomaly pattern. The ongoing dynamic hydrocarbon migration process has been directly imaged by seismic data for the first time.